2012
DOI: 10.1007/s11803-012-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structural characteristics distribution on strength demand and ductility reduction factor of MDOF systems considering soil-structure interaction

Abstract: It is known that structural stiffness and strength distributions have an important role in seismic response of buildings. The effect of using different code-specified lateral load patterns on seismic performance of fixedbase buildings have been investigated by researchers during the past two decades. However, no investigation has been carried out for the case of soil-structure systems yet. In the present study, through intensive parametric analyses of 21600 linear and nonlinear MDOF systems and considering fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…observation is opposite to conclusions made by Ganjavi and Hao [38], where the concentric pattern was found to yield the lowest strength demand. The reason for this difference is attributed to different definitions of strength demand used in the two studies.…”
Section: Effects Of Design Lateral Load Patterncontrasting
confidence: 99%
See 2 more Smart Citations
“…observation is opposite to conclusions made by Ganjavi and Hao [38], where the concentric pattern was found to yield the lowest strength demand. The reason for this difference is attributed to different definitions of strength demand used in the two studies.…”
Section: Effects Of Design Lateral Load Patterncontrasting
confidence: 99%
“…For each storey in a given simulation, the peak storey ductility ratio was calculated as the maximum shear deformation divided by the yield deformation. The maximum value of the peak storey ductility ratios was used as the ductility demand of an MDOF building, as done by Santa-Ana and Miranda [13], Moghaddam and Mohammadi [37], and Ganjavi and Hao [38]. It should be mentioned that this ductility demand excludes the effects of the rigid body movements caused by the translation and rotation of the foundation and, therefore, can directly reflect the expected damage of the superstructure.…”
Section: Modelling Parameters and General Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that the lateral LP can considerably affect the required inelastic strength demands for both fixed‐base and SSI systems. This finding is in complete agreement with the results presented by Ganjavi and Hao and Lu et al for shear‐building structures considering SSI effects.…”
Section: Ductility Reduction Factor For Soil‐mdof Structure Systemssupporting
confidence: 93%
“…Ceylan et al [33] estimated the strength reduction factor for prefabricated industrial structures having a single story, one and two bays. Ganjavi and Hao [34] studied the seismic response of linear and nonlinear MDOF systems subjected to a group of earthquakes recorded on alluvium and soft soils, considering different shear strength and stiffness distribution patterns. Kumar et al [35,36] investigated the influence of the frequency content of ground motions, as well as structural parameters and the level of inelasticity, on the inter-story shear and inter-story drift demands in frames designed according to Eurocode 8.…”
Section: Literature Reviewmentioning
confidence: 99%